2021
DOI: 10.1108/jd-01-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the academy: a conceptual framework for understanding trust on academic web profiles

Abstract: PurposeInstitutional and commercial web profiles that provide biobibliographic information about researchers are used for promotional purposes but also as information sources. In the latter case, the profiles' (re)presentations of researchers may be used to assess whether a researcher can be trusted. The article introduces a conceptual framework of how trust in researchers may be formed based on how the researchers' experiences and achievements are mobilized on the profiles to tell a multifaceted story of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Wu et al (2017) confirmed these reasons by conducting semistructured interviews with researchers at American institutions hosting institutional repositories, in addition to literature-seeking activity. Francke (2022) provides evidence that researchers use profiles for promotion and as a list of scholarly output. When faculty use profiles to list scholarly output, this, Francke argues, builds trust and credibility.…”
Section: Reasons For Using Researcher Profile Systemsmentioning
confidence: 99%
“…Wu et al (2017) confirmed these reasons by conducting semistructured interviews with researchers at American institutions hosting institutional repositories, in addition to literature-seeking activity. Francke (2022) provides evidence that researchers use profiles for promotion and as a list of scholarly output. When faculty use profiles to list scholarly output, this, Francke argues, builds trust and credibility.…”
Section: Reasons For Using Researcher Profile Systemsmentioning
confidence: 99%
“…A strong online presence is considered important by many academics as a channel to disseminate research publications and other achievements, connect with peers and for general outreach (Cheek and Øby, 2019; Greifeneder et al ., 2018; Mas-Bleda and Aguillo, 2013). A central element in researchers' online presence is the academic web profile , which is a ubiquitous genre of scholarly life (Hyland, 2011) that allows researchers “to display information both about themselves and their publications to various audiences online” (Francke, 2022, pp. 192–193).…”
Section: Introductionmentioning
confidence: 99%
“…192–193). The academic web profile can help researchers promote themselves and their work and serve as an information source for various stakeholders such as students, research funding agencies, professionals, journalists and policymakers (Francke, 2022). Researchers can choose from various channels when presenting themselves online: web profiles on institutional websites (universities, research groups, etc.…”
Section: Introductionmentioning
confidence: 99%